Pembuatan Aplikasi Saat Teduh Pada Mobile Device Berbasis Android - Timothy Tiovano Notopuro; Alexander Setiawan; Justinus Andjarwirawan (Jurnal Infra, 2016)
Quiet time is an activity of Christians to pray, worship God and reading the Bible personally are generally done in the morning before any activity begins. But many Christians overlook a quiet time because often they do not know what to do for a quiet time as a song to be sung, and devotional material must be read.In this study conducted by making quiet time Android-based applications with Phonegap technology. This app has a feature to help users to have a quiet time and users can discuss with other users on matters relating to the Christian life and the truth of the BibleBased on the results of the implementation and testing that has been done, the application can display the material in the form of devotional quiet time every day, provide a video link song material for quiet time, and provide features to users in order to have discussions with the use of technology Google Cloud Messaging.